Regorafenib in Refractory Metastatic Colorectal Cancer: A Multi-Center Retrospective Study - Xu, Donghao; Liu, Yu; Tang, Wentao; Xu, Lingsha; Liu, Tianyu; Jiang, Yudong; Zhou, Shizhao; Qin, Xiaorui; Li, Jisheng; Zhao, Jiemin; Ye, Lechi; Chang, Wenju; et al. (Frontiers in Oncology, 2022)
Background Regorafenib improves overall survival (OS) and progression-free survival (PFS) in patients with refractory metastatic colorectal cancer (mCRC). Here we report the treatment patterns of regorafenib in the third- or late-line setting for mCRC in four centers in China. Patients and Methods Patients with refractory mCRC in four centers in China administered regorafenib from February 1, 2018 to June 31, 2021 were enrolled. Patients were grouped into 3 cohorts, including the monotherapy (regorafenib alone), chemo (regorafenib plus chemotherapy) and immune (regorafenib plus anti-PD1 (programmed cell death 1) antibodies) groups. Demographic, clinical, survival and safety data were retrospectively analyzed. Results A total of 177 patients were included in this study. Of them, 116 (65.5%) were treated with regorafenib alone, while 28 (15.9%) and 33 (18.6%) were administered regorafenib plus chemotherapy and anti-PD1 antibodies, respectively. The median followup time was 9.2 months. The disease control rate (DCR) was 40.7%. The median PFS (mPFS) was 2.43 months and the median OS (mOS) was 12.2 months. The immune group had longer median PFS ( 3.5 m vs. 2.2 m, p=0.043) compared with the monotherapy group. Patients administered regorafenib plus chemotherapy had longer median OS (15.9 m vs. 8.4 m, p=0.032) compared with the monotherapy group. Patients who began regorafenib treatment at 120 mg had longer median PFS and OS compared with those who began at 80 mg (PFS: 3.7 m vs. 2.0 m; p<0.001; OS: 13.4 m vs. 10.2 m; p=0.005). Patients with a final dose of 120 mg had longer median PFS and OS compared with the 80 mg or less group (PFS: 5.0 m vs. 2.3 m; p=0.045; OS: UR (unreach) vs. 10.9 m; p=0.003). There were 87.0% (154/177) patients experiences AEs. Three groups had similar rates of AEs (86.2% vs. 89.3% vs. 87.9%; p=0.89). Conclusion Patients administered regorafenib alone or regorafenib in combination with other agents were relieved to some extent, with a disease control rate of 40.7%. Regorafenib plus anti-PD1 antibodies showed better PFS, while regorafenib plus chemotherapy had the most benefit in OS. There was no significant difference among three groups in terms of AEs.